Geopolymer concrete incorporating recycled aggregates: A comprehensive review - Thomas, Blessen Skariah; Yang, Jian L.; Bahurudeen, A.; Chinnu, S. N.; Abdalla, Jamal A.; Hawileh, Rami A.; Hamada, Hussein Mahmood (Elsevier Ltd, 2022)
Several industrial by-products are extensively used again as a supplementary cementitious material or aggregates in the interest to reduce environmental footprints in terms of energy depletion, pollution, waste disposition, resource depletion, and global warming related with conventional cement. A remarkable quantity of industrial scrap materials, primarily designated as construction and demolition waste from the construction industry, has transformed into crucial apprehension of governments. In the recent past, substantial explorations have been accomplished to appreciate the distinct characteristics of concrete, employing recycled aggregates from construction and demolition waste. Geopolymer composite is a new cementitious material, and it appears to be a potential replacement for conventional cement concrete. This paper summarises the previous research concerning the utilisation of recycled aggregate as a partial or complete supplants for conventional aggregates in geopolymer concrete. The influence of recycled aggregate addition on the fresh and hardened properties of geopolymer concrete is comprehensively reviewed in this paper. The studies suggest significant improvement in the workability on addition of recycled aggregates to geopolymer concrete. However, the addition results in increased water absorption and sorptivity.